Validity of Elastography in Differentiating Benign and Malignant Thyroid Nodules, Keeping Histopathology as Gold Standard - Asadullah, Sajad Ahmad, Asia Ajmal, Amina Shahid, Aaisha Qadir, Aisha Khalid, Abdul Qahar, Rida Naz, Fakhra Soomro, Masood Ur Rehman (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Elastography is a method recently being used in the evaluation of thyroid nodules by comparing tissue elasticity. The aim of this study was to determine the diagnostic accuracy of elastography in differentiation between benign and malignant thyroid nodules, taking histopathology as gold standard. Methods: Total of 50 patients with palpable thyroid nodule of any size of age 20-60 years of either gender were included. elastography was performed in every patient by using a high resolution unit with a linear array probe centered at 7.5 MHz, elastography was performed in every patient by a consultant radiologist benign or malignant thyroid nodules was noted. Elastography findings were compared with histopathology report Results: All the patients were subjected to strain ultrasound elastography. USG supported the diagnosis of malignant thyroid nodules in all 50 patients. Histopathology confirmed malignant thyroid nodules in 46 (true positive) cases where as 4 (false positive) had no malignant lesion on histopathology. In USG negative patients, 47 were true negative while 2 were false negative. Overall sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of strain ultrasound elastography in differentiation between benign and malignant thyroid nodules, taking histopathology as gold standard is 90.0%, 90.30%, 92.31%, 94.77% and 93.18% respectively Conclusion: According to this study, strain ultrasound elastography is the non-invasive modality of choice with high diagnostic accuracy in diagnosing malignant thyroid nodules. Keywords: Thyroid cancer, Ultrasound elastography, Sensitivity, Specificity